Outcomes of outpatient parenteral antimicrobial therapy (OPAT) for urinary tract infections – A single center retrospective cohort study - Sadia Shakoor; Oyewole Chris Durojaiye; Paul J. Collini (Clinical Infection in Practice, 2023)
Background: Outpatient parenteral antimicrobial therapy (OPAT) is widely used to safely administer intravenous antibiotics in the outpatient setting. However, there are risks of treatment failure and clinical complications. We evaluate the outcomes of episodes of urinary tract infection (UTI) treated through OPAT at a large tertiary referral center in the UK. Methods: We retrospectively reviewed patient records of episodes of UTI treated for ≥ 2 days at the Sheffield Teaching Hospitals OPAT unit from 2017 to 2021. We defined OPAT and infection failure as unplanned 30-day hospital readmissions and symptomatic non-improvement, respectively. Univariate and multivariate logistic regression analyses were performed to analyze predictors of these outcomes. Results: 162 episodes of UTI in 115 patients were analyzed. OPAT failure was observed in 16.0 % (n = 26) of episodes, while infection remained unresolved in 8.0 % (n = 13) of episodes. Urolithiasis was an independent risk factor of both OPAT (odds ratio [OR], 4.3; 95 % confidence interval [CI], 1.2–16.1; p = 0.03) and infection failure (OR, 5.9; 95 % CI, 1.2–29.9; p = 0.03). Prior hospitalization also increased the risk of both OPAT (OR, 4.4; 95 % CI, 1.1–18.7; p = 0.04) and infection failure (OR, 8.0, 95 % CI, 1.3–78.4; p = 0.04). Conclusions: These results can assist clinicians at commencement of OPAT to identify patients at high risk of treatment failure. Wider network studies are required to further elicit the role of urolithiasis and its treatment to improve outcomes of UTI management in OPAT.